Alcoholic cirrhosis is a good indication for liver transplantation, even for cases of recidivism. Issue 3 (1st September 1999) - Pageaux, G-P; Michel, J; Coste, V; Perney, P; Possoz, P; Perrigault, P-F; Navarro, F; Fabre, J-M; Domergue, J; Blanc, P; Larrey, D
Abstract : BACKGROUND/AIMS: Alcoholic cirrhosis remains a controversial indication for liver transplantation, mainly because of ethical considerations related to the shortage of donor livers. The aim of this study was to review experience to date, focusing on survival rates and complications, and the effect of alcohol relapse on outcome and alterations in marital and socioprofessional status. METHODS: The results for 53 patients transplanted for alcoholic cirrhosis between 1989 and 1994 were compared with those for 48 patients transplanted for non-alcoholic liver disease. The following variables were analysed: survival, rejection, infection, cancer, retransplantation, employment and marital status, alcoholic recurrence. The same variables were compared between alcohol relapsers and non-relapsers. RESULTS: Recovery of employment was the only significantly different variable between alcoholic (30%) and non-alcoholic patients (60%). Two factors influenced survival in the absence of alcohol recidivism: age and abstinence before transplantation. For all other variables, there were no differences between alcoholic and non-alcoholic patients, and, within the alcoholic group, between relapsers and non-relapsers. The recidivism rate was 32%. CONCLUSION: The data indicate that liver transplantation is justified for alcoholic cirrhosis, even in cases of recidivism, which did no affect survival and compliance with the immunosuppressive regimen. These good results should help in educating the general population about alcoholic disease.